Laboratory scale modelling for offshore geotechnical problems - Byrne, B (2014)
Physical modelling is an important tool in the armoury of the geotechnical engineer, particularly for complex offshore engineering problems. It is used in both the research environment and in the commercial sector. Physical models can provide insight into new phenomena, aiding theoretical developments, and providing a benchmark for design equations. They can also add value to the design process by helping to mitigate risk. In constructing the experimental testing program there must be careful consideration of scaling issues, as it is not usually possible (or desirable) to carry out full scale testing in the laboratory (or in the field). Dimensional analysis allows the key variables controlling the problem to be determined, from which the scalability of the problem can be judged. Often scaling all aspects of the problem is not possible and so engineering judgement is needed to assess what the important issues are. This paper explores contributions made by physical modelling on the laboratory floor, and focuses on problems related to offshore geotechnical engineering. The paper looks at complexity of testing as it moves from one degree of freedom through to six degrees of freedom. The paper concludes by describing some of the current challenges in experimental modelling, and theoretical interpretation, for offshore problems. © 2010 Taylor and Francis Group, London.